Nonwage Benefits in a Simultaneous Model of Wages and Hours: Labor Supply Functions of Young Females - Vella, Francis (Journal of Labor Economics, 1993)
This article argues that the negative relationship between weekly hours worked and the gross hourly wage rate is due to the provision of fringe benefits. As the total weekly wage increases, employers and employees avoid taxation by substituting wages with nontaxable, nonwage benefits. I produce a wage that incorporates the benefit effects and estimate the corresponding labor-supply elasticities. An estimator is presented for the wage/hours market locus and the structural labor-supply function. An empirical application indicates that an estimated negative labor-supply elasticity associated with the observed gross wage is reversed when the adjusted wage is employed.